Inovasi Platform Integrasi Belanja Pemerintah melalui Digipay “Pemberdayaan UMKM Perspektif New Public Governance” - Styadi, Aris (IPM2KPE, 2024)
This study aims to analyze the effectiveness of Digipay in improving the efficiency, transparency, and accountability of state spending management, as well as evaluating its role in the transformation of digital-based public governance involving the concept of New Public Governance. This study uses a qualitative methodology based on secondary data to analyze the implementation of the Digital Payment (Digipay) platform by the Ministry of Finance in government spending. The results of the study show that the implementation of Digipay has received a positive response from various parties, with significant transaction values ​​since its initial implementation in 2021. Digipay promotes public innovation through governance transformation that includes the concept of co-production, hybrid organizations, key competencies, accountability, and operational evaluation based on the New Public Governance approach. Sipmulan, Digipay is an effective innovation in strengthening the digital economy, supporting bureaucratic efficiency, and increasing regional economic competitiveness. Continuous support from the government, banking, and the community is needed to optimize the implementation and expand the benefits of this system. Keywords: Innovation, Public Services, New Public Governance